Скорость вращения жидкого металла в кристаллизаторе с синхронным электромагнитным перемешивателем - Виштак, Т.В.; Карлов, А.Н.; Кондратенко, И.П.; Ращепкин, А.П. (Інститут електродинаміки НАН України, 2014)
Разработан итерационный численно-аналитический метод для расчета распределения скорости вращения жидкого металла в кристаллизаторе с синхронным электромагнитным перемешивателем. Приведены для принятого конструктивного исполнения кристаллизатора результаты иллюстративных расчетов распределения скорости вращения жидкого металла и установлены функциональные зависимости максимальной скорости металла у фронта кристаллизации на выходе из перемешивателя и его мощности от частоты тока питания. Розроблено ітераційний чисельно-аналітичний метод розрахунку розподілу швидкості обертання рідкого металу в кристалізаторі з синхронним електромагнітним перемішувачем. Наведено для прийнятого конструктивного виконання результати ілюстративних розрахунків швидкості обертання рідкого металу і встановлено функціональні залежності максимальної швидкості обертання металу біля фронту кристалізації на виході з перемішувача та його потужність від частоти струму живлення. Developed an iterative numerical-analytical method for calculating the distribution of the rotational speed of the liquid metal in the mold with synchronous electromagnetic a stirrer. Because the time-averaged the azimuthal component of the bulk electrodynamic forces in the liquid metal during its acceleration depends on the speed, determination the time dependence of the rotational speed of the metal in the mold liner is performed by method of iteration. All other conditions being equal, the magnetic field in the mold sleeve, determining the force of the direct effect on the molten metal, essentially depends on the mode of the stirrer For an adopted design of the stirrer is retrieved the distribution of radial component of induction in modes of a underexcitation and overexcitationю It is shown that under the same magnets and stator currents, it is possible to significantly improve the resulting magnetic field in a liquid metal that is in the mode underexcitation. For the accepted embodiment of the mold shows the results of the illustrative calculations of the distribution of the rotational speed of the liquid metal and set the functional dependence of the maximum velocity of the metal near the crystallization front at the exit of the stirrer and him the power on the frequency a supply current.